Perancangan Sistem Tata Kelola Keuangan Berbasis Anggaran Universitas Atma Jaya Makassar - Gormantara, Alfredo (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2017)
This thesis focuses on the development of financial management system of budgeting and financing that is integrated and connected. To achieve these objectives, it is necessary to develop to integrate previously created systems into one large and integrated system part so that systems that can support the budgeting, financing and management processes of university finance that include the principles of SNPT are accountability and transparency. The authors hope the financial system of budgeting and financing can help to manage finance, budgeting and financing are integrated and comprehensive and provide transparency in financial management at Atma Jaya University of Makassar.Â Keywords: : Accountability, Finance, Management, Transparency, University.